Universal gestational diabetes screening and antepartum stillbirth rates in Austria—A population‐based study. (23rd February 2022) - Muin, Dana A.; Pfeifer, Bernhard; Helmer, Hanns; Oberaigner, Wilhelm; Leitner, Hermann; Kiss, Herbert; Neururer, Sabrina
Abstract: Introduction: Occult or untreated gestational diabetes (GDM) is a well‐known risk factor for adverse perinatal outcomes and may contribute to antepartum stillbirth. We assessed the impact of screening for GDM on the rate of antepartum stillbirths in non‐anomalous pregnancies by conducting a population‐based study in 974 889 women in Austria. Material and Methods: Our database was derived from the Austrian Birth Registry. Inclusion criteria were singleton live births and antepartum stillbirths ≥24 +0 gestational weeks, excluding fetal congenital malformations, terminations of pregnancy and women with pre‐existing type 1 or 2 diabetes. Main outcome measures were (a) overall stillbirth rates and (b) stillbirth rates in women at high risk of GDM (i.e., women with a body mass index ≥30 kg/m 2, history of previous intrauterine fetal death, GDM, previous macrosomic offspring) before (2008–2010, "phase I") and after (2011–2019, "phase II") the national implementation of universal GDM screening with a 75 g oral glucose tolerance test in Austrian pregnant women by 2011. Results: In total, 940 373 pregnancies were included between 2008 and 2019, of which 2579 resulted in intrauterine fetal deaths at 33.51 ± 5.10 gestational weeks. After implementation of the GDM screening, a statistically significant reduction in antepartum stillbirth rates among non‐anomalous singletons was observed only in women at high risk for GDM (4.10‰ [95% confidence interval (CI) 3.09–5.43] in phase I vs. 2.96‰ [95% CI 2.57–3.41] in phase II; p  = 0.043) but not in the general population (2.76‰ [95% CI 2.55–2.99] in phase I vs. 2.74‰ [95% CI 2.62–2.86] in phase II; p  = 0.845). The number needed to screen with the oral glucose tolerance test to subsequently prevent one case of (non‐anomalous) intrauterine fetal death was 880 in the high‐risk and 40 000 in the general population. Conclusions: The implementation of a universal GDM screening program in Austria in 2011 has not led to any significant reduction in antenatal stillbirths among non‐anomalous singletons in the general population. More international data are needed to strengthen our findings.